SYSTBMA TICS AND COMPARATIVE OSTEOLOGY OF INDIAN LIZARD FISHES (SAURIDA SPP.) - Rao, K Venkata Subba (Indian Journal of Fisheries, 2011)
A study of the systematics and ost’eology of the lizard fishes of the genus Saurida was undertaken at Waltair in connection with the investigation on their biology. The investigation covered mainly the continental shelf between Lat. 16Â° 40’ Nand 21Â°00’N along the north western part of the Bay of Bengal. Of the four species of the genus Saurida namely, S. tumbil,S. undosquamis, S. longimanus and S. gracilis occurring in Indian waters, only the first three species were recorded during the peried of this investigation (1964 to 1970) from the north-western part of the Bay of Bengal.